Kuria Male Adolescents and Career Choice Experiences: The Role of Careers Knowledge and Significant Others - Onditi, Hezron Z. (Papers in Education and Development, 2018)
Given their historical attachment to a career in the armed forces, this study sought to uncover knowledge of young Tanzanian Kuria males on identifying careers, sources of career information and the influence of significant others on their choice of career. A total of 258 male students (from Tarime district) responded to a questionnaire and focus group discussions. It was revealed that young Kuria males have a good knowledge of the different careers available in the world of work, and their attachment to a career in the army has little to do with career illiteracy. To young Kuria males, parents and relatives appear to have a strong direct and indirect influence on their favouring a career in the armed forces. Key words: career, career choice, and significant others